Reviews of Environmental Contamination and Toxicology Volume 218 - Whitacre, David M.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
CONTENTS FOREWORD PREFACE Human Pharmaceuticals in the Aquatic Environment: A Review of Recent Toxicological Studies and Considerations for Toxicity Testing John M. Brausch, Kristin A. Connors, Bryan W. Brooks and Gary M. Rand Fish Metalloproteins as Biomarkers of Environmental Contamination Rachel Ann Hauser-Davis, Reinaldo Calixto de Campos and Roberta Lourenço Ziolli Spatial Distribution of Arsenic in Groundwater of Southern Nepal Ishwar Chandra Yadav, Surendra Singh, Ningombam Linthoingambi Devi, Devendra Mohan, Madhav Pahari, Pratap Singh Tater, Birendra Man Shakya Propoxur: A Novel Mechanism for Insecticidal Action and Toxicity Peter Kovacic and Ratnasamy Somanathan
Foreword -- Preface -- Human Pharmaceuticals in the Aquatic Environment: A Review of Recent Toxicological Studies and Considerations for Toxicity Testing -- Fish Metalloproteins as Biomarkers of Environmental Contamination -- Spatial Distribution of Arsenic in Groundwater of Southern Nepal -- Propoxur: A Novel Mechanism for Insecticidal Action and Toxicity -- Index.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Ecotoxicology; Environmental Management; Waste Management/Waste Technology